Collision training prescription in collision by elite coaches: A qualitative study - Williams, Mogamat (Department of Health and Rehabilitation Sciences, 2024)
Background Collision training is essential for coaches to prepare athletes for competition. However, there is a lack of understanding about how coaches approach collision training prescription. While exercise prescription principles such as frequency, intensity, type, duration, and volume are well-established in muscle resistance literature, their application to collision training is limited. In both team and individual collision sports, athlete collisions are the leading cause of injuries, affecting player wellbeing and team performance significantly. Although injuries occur less frequently during training compared to matches, the risk of training-related injuries remains a concern. To enhance performance and reduce injuries in collision sports, further research is required in this field. Aim and Objectives This dissertation aimed to explore the perspectives of elite coaches regarding collision training prescription. The objectives were to: a) explore the current collision training perspectives of elite collision coaches for collision training planning, necessity, and risk; b) describe the established exercise prescription parameters such as frequency, intensity, duration, activity, and volume regarding collision training prescription; and c) describe differences in collision prescription across the participants. Methodology We conducted a qualitative descriptive study using semi-structured interviews via Zoom. We analysed the interview data systematically using thematic analysis and the NVivo 12 software. We recruited six elite male collision coaches, including three from rugby union, two from mixed-martial arts (MMA), and one from boxing, using purposeful sampling via social media. Coaches who did not provide informed consent were excluded. Results In theme one, we found that elite coaches had prior experience as elite athletes, influencing their views on collision training planning through personal experience and interactions with fellow coaches. Theme two revealed that coaches took a comprehensive approach to prescribing collision training. They considered athlete conditioning, skill development, and realistic match simulations. They also adjusted collision training intensity, volume, frequency, and duration based on the competition date. Differences were noted between sports, with MMA and boxing having more frequent and longer collision training sessions compared to rugby union. Protective equipment was consistently emphasised. In theme three, coaches adapted collision training when athletes were injured and consulted other specialists. They used both subjective measures, like verbal intensity scales, and objective tools, such as Global Positioning System (GPS) in rugby union, for monitoring and adjustments. This approach ensured safety and performance in collision sports. Conclusion This dissertation was the first multinational study researching the perspectives of elite coaches from diverse sporting backgrounds regarding collision training. Over time, collision training methods have evolved, especially in rugby union, where coaches now advocate for shorter yet more intense collision sessions, all while prioritising the use of protective gear. This shift towards shorter training durations underscores a growing emphasis on athlete well-being. While the direct practical application and generalisability of these findings to the broader coaching community may be limited, this dissertation serves as a valuable resource for gaining an evidence-based insight into how coaches approach collision training prescription. Future research should progress into stage three of the Translating Research into Injury Performance Practice (TRIPP) framework and should also consider the development of comprehensive injury prevention programmes specifically tailored for collision training prescription in various sports.